Refeeding syndrome in the gastroenterology practice: how concerned should we be?. Issue 11 (November 2018) - Nunes, Gonçalo; Brito, Mariana; Santos, Carla Adriana; Fonseca, Jorge
Abstract : Clinical nutrition is emerging as a major area in gastroenterology practice. Most gastrointestinal disorders interfere with digestive physiology and compromise nutritional status. Refeeding syndrome (RS) may increase morbidity and mortality in gastroenterology patients. Literature search using the keywords "Refeeding Syndrome", "Hypophosphatemia", "Hypomagnesemia" and "Hypokalemia". Data regarding definition, pathophysiology, clinical manifestations, risk factors, management and prevention of RS were collected. Most evidence comes from case reports, narrative reviews and scarse observational trials. RS results from the potentially fatal shifts in fluid and electrolytes that may occur in malnourished patients receiving nutritional therapy. No standard definition is established and epidemiologic data is lacking. RS is characterized by hypophosphatemia, hypomagnesemia, hypokalemia, vitamin deficiency and abnormal glucose metabolism. Oral, enteral and parenteral nutrition may precipitate RS. Awareness and risk stratification using NICE criteria is essential to prevent and manage malnourished patients. Nutritional support should be started using low energy replacement and thiamine supplementation. Correction of electrolytes and fluid imbalances must be started before feeding. Malnourished patients with inflammatory bowel disease, liver cirrhosis, chronic intestinal failure and patients referred for endoscopic gastrostomy due to prolonged dysphagia present high risk of RS, in the gastroenterology practice. RS should be considered before starting nutritional support. Preventive measures are crucial, including fluid and electrolyte replacement therapy, vitamin supplementation and use of hypocaloric regimens. Gastroenterology patients must be viewed as high risk patients but the impact of RS in the outcome is not clearly defined in current literature.